95: Neonatal Outcomes in Infants <29 Weeks Gestation in Relation to Maternal Hypertension and Smoking Status. Issue 6 (1st June 2014) - Yusuf, K; Nair, V; Alshaikh, B; Hasan, SU; Lodha, A; Silva, O da; Alvaro, RE; Lee, SK; Shah, PS
Abstract: BACKGROUND: Maternal hypertension and cigarette smoking during pregnancy are associated with adverse neonatal outcomes. Paradoxically, smoking during pregnancy is associated with a reduced incidence of gestational hypertension. However, mothers who smoke during pregnancy and develop hypertension have worse pregnancy outcomes as compared to mothers who only have hypertension or non-smoking normotensive mothers. There is little data on neonatal outcomes of infants born to mothers with hypertension who also smoke. OBJECTIVES: To study the outcomes of infants of mothers with hypertension who smoke. DESIGN/METHODS: Using the Canadian Neonatal Network Database, we analyzed the outcomes of infants <29 weeks GA admitted to Canadian NICUs from 2003–2012. Infants were divided into four groups. Group 0 comprised infants of hypertensive mothers who smoked, group 1 infants of non-smoking hypertensive mothers, group 2 infants of normotensive mothers who smoked and group 3 infants of normotensive non-smoking mothers. Composite outcome of neonatal mortality or any of the major morbidities grade 3/4 intraventricular hemorrhage (IVH), periventricular leukomalacia (PVL), retinopathy of prematurity (ROP) > stage 2, late onset sepsis (LOS) or bronchopulmonary dysplasia (BPD) was assessed using a multivariable model. RESULTS: Of the 12, 307 eligible infants, 172 were in group 0, 1689 in group 1, 1535 in group 2 and 8911 in group 3. Adjusted ORs with 95% CIs with reference to group 3 (normotensive, non-smokers) are reported in Table 1 . CONCLUSIONS: Infants of hypertensive mothers, whether smokers or non-smokers, were associated with higher rates of BPD. Smoking cessation campaigns during pregnancy are needed for both maternal and neonatal benefits.,